2021
DOI: 10.1007/s00259-021-05603-w
|View full text |Cite|
|
Sign up to set email alerts
|

EANM procedure guidelines for brain PET imaging using [18F]FDG, version 3

Abstract: The present procedural guidelines summarize the current views of the EANM Neuro-Imaging Committee (NIC). The purpose of these guidelines is to assist nuclear medicine practitioners in making recommendations, performing, interpreting, and reporting results of [18F]FDG-PET imaging of the brain. The aim is to help achieve a high-quality standard of [18F]FDG brain imaging and to further increase the diagnostic impact of this technique in neurological, neurosurgical, and psychiatric practice. The present document r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
102
0
10

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 134 publications
(113 citation statements)
references
References 155 publications
(210 reference statements)
1
102
0
10
Order By: Relevance
“…While confirming the results of previous preclinical work of similar design 13 using high target-to-background ratios, we also found the advantages of small-voxel reconstruction to translate as well towards lower ratios, resembling realistic clinical circumstances when focused imaging is performed for limited body sections in extended duration, such as parathyroid or brain PET. 15 , 16 However, these findings may translate to acquisitions typically used for whole-body imaging as well, as recently shown in a preclinical study. 17 …”
Section: Discussionmentioning
confidence: 93%
“…While confirming the results of previous preclinical work of similar design 13 using high target-to-background ratios, we also found the advantages of small-voxel reconstruction to translate as well towards lower ratios, resembling realistic clinical circumstances when focused imaging is performed for limited body sections in extended duration, such as parathyroid or brain PET. 15 , 16 However, these findings may translate to acquisitions typically used for whole-body imaging as well, as recently shown in a preclinical study. 17 …”
Section: Discussionmentioning
confidence: 93%
“…Participants had to fast for at least 5.5 h before the start of the PET/MRI scan (except for unsweetened water), according to [ 18 F]FDG procedure guidelines 84 . The radiotracer 2-[ 18 F]fluoro-2-deoxy-D-glucose ([ 18 F]FDG) was administered in a bolus (510 kBq per kg per frame for 1 min) plus infusion protocol (40 kBq per kg per frame for 51 min) with a perfusion pump (Syramed µSP6000, Arcomed, Regensdorf, Switzerland) which was kept in an MRI-shield (UniQUE, Arcomed) 77 .…”
Section: Methodsmentioning
confidence: 99%
“…The pons was selected as the intensity normalization region to ensure the consistency of the data. It is reported that the pons is the best brain region for the normalization of intensity on the 18 F-FDG-PET scans of the brain [ 20 ], which can be adopted for visual and semiquantitative analysis of brain 18 FDG-PET imaging associated with other diseases in the absence of any pathological involvement [ 21 ]. However, the current international stable and reliable region for brain PET image analysis related to endodontic pain still needs further research.…”
Section: Discussionmentioning
confidence: 99%